Representations of the concept of pedagogical supervision among teachers - Dias, R.; Oliveira, A. (Proceedings of the 3° International Conference on Human and Social Sciences (ICHSS 2013), 2013)
Considering teaching and education, the challenges we face daily are increasingly relevant, for all agents involved. Given the time that children spend in school, a good pedagogical relationship, between teachers and students, is very important in the development of children. So, teachers seek for strategies to make the process of teaching and learning more engaging for students, and more rewarding for themselves. This empirical study was developed within the scope of the theory of social representations (Moscovici, 1961/1976). We aimed to understand, first of all, the way how teachers (N=176), men and women, of the 1st and 2nd stages of basic education, in Portugal, represent the concept of pedagogical supervision, and also the way how the representations found can be related to the way they usually feel in classroom. The data was gathered using free associations of words, derived from open questions that were individually made, in an questionnaire (e.g., ‘Pedagogical supervision makes me think of...’; or ‘Pedagogical supervision makes me feel...’). Results were examined through the technique of factorial analysis of correspondences (FCA). Among the main findings, it was verified that, in general, the teachers of the 2nd stage feel more active than those of the 1st stage, linking the concept of pedagogical supervision with a helpful process that is led by someone with more experience and scientific knowledge. Women, compared to men, demonstrate more nervousness and anxiety, when confronted with pedagogical supervision, tending to anchor the supervision with the evaluation process that all teachers have throughout their career.